DIRICHLET PROBLEM IN A CYLINDRICAL AREA FOR ONE CLASS OF MULTIDIMENSIONAL ELLIPTIC-PARABOLIC EQUATIONS - S.A. Aldashev; M.N.Maikotov (Academic Scientific Journal of Computer Science, 2019)
Boundary-value problems for degenerate elliptic-parabolic equations on the plane are studied quite well ([1]). The correctness of the Dirichlet problem for degenerate multidimensional elliptic-parabolic equations with degeneration of type and order was established in [3]. In the work for multidimensional elliptic-parabolic equations with degeneration of type and order, the solvability is shown and an explicit form of the classical solution of the Dirichlet problem is obtained.